Tourism, ICT and inclusive development: Global evidence - Tii Njivukuh Nchofoung; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
This study empirically examines the effect of tourism and ICT on inclusive development. Inclusive development is approached as human development adjusted for environmental sustainability; ICT is based on mobile phones subscription rate, internet penetration and fixed broadband subscription and a composite indicator of these, while tourism is approached as a the number of arrivals. The data are collected for 142 countries globally between the 2000- 2019 period and the regression methodologies involve the POLS, the Driscoll and Kraay estimator, the Mean Group, the System GMM and the fixed effects Tobit regression. The results of the linear model show that, tourism enhances sustainable development and ICT has a negative significant effect. While the effect of tourism is robust across income groups, regional groupings and regression methodologies, the effect of ICT varies across these different specifications. When non-linearity is considered, the effects of both ICT and tourism are positive and robustly non-linear. The non-linear effect of tourism is not however feasible across income groups. Besides, while the effect of tourism is positively and non-lineally related to sustainable development in politically-stable economies, the effect is nonsignificant in unstable economies. From the results, countries should seize the opportunity offered by the tourism sector and ICT as effective policy tools towards sustainable development. In this regard, countries should invest in both ICT and tourism while observing the thresholds where complementary policies should be used. Also, politically-unstable economies should engage in peace talks such that they could join their politically-stable counterparts in benefiting from the positive economic effects offered by tourism and ICT.
Keywords: G20; I10; I32; O40; Z32; 330; Inclusive development; ICT; tourism